Biodegradable Polymeric Nano-composites for Microbial Growth Control and Wound Healing - Pandey, Vivek Kumar (IIT(BHU) Varanasi, 2020)
Abstract is available in content.
Keywords: Biodegradable; Polymeric; Nano-composites for Microbial Growth Control; Wound Healing